Acute-phase proteins during inflammatory reaction by bacterial infection: Fish-model - Charlie-Silva, Ives [UNESP]; Klein, Andre; Gomes, Juliana M. M.; Prado, Ed J. R. [UNESP]; Moraes, Alessandra C. [UNESP]; Eto, Silas F. [UNESP]; Fernandes, Dayanne C. [UNESP]; Fagliari, José J. [UNESP]; Junior, José D. Corrêa; Lima, Carla; Lopes-Ferreira, Mônica; Conceição, Katia; et al. (Springer Nature, 2019)
Acute-phase protein (APPs) serum levels have been studied in many human diseases, and their components contribute to host defense during the evolution of infectious diseases by acting as part of the innate immune system. Based on the importance of establishing new experimental models, the present investigation evaluated the modulation of APPs following inflammatory stimulus by the inoculation of Aeromonas hydrophila in tilapias. Fish were sampled 6 and 24 hours post-infection. Tilapias presented increase of positive APPs such as ceruloplasmin, haptoglobin, alpha-2-macroglobulin and complement C3, as well as decrease of negative APPs such as albumin and transferrin. The protein response of tilapias during the course of bacterial infection showed correlation with the kinetics of cellular accumulation in the inflamed focus with significant increase of granulocytes, thrombocytes, lymphocytes and macrophages. However, granulocytes were the predominant cells, associated with increment in the reactive oxygen species (ROS) production. Showing responses similar to those observed in humans, the modulation of APPs and the kinetics of cellular accumulation in the exudate demonstrate the feasibility of this alternative experimental model for advances and studies to understand changes in pathophysiological mechanisms of acute inflammatory reaction due to bacterial infection.